Respuesta :

Answer:

x = -1/2 , y = -1

Step-by-step explanation:

Solve the following system:

{y = 4 x + 1 | (equation 1)

{y = 2 x | (equation 2)

Express the system in standard form:

{-(4 x) + y = 1 | (equation 1)

{-(2 x) + y = 0 | (equation 2)

Subtract 1/2 × (equation 1) from equation 2:

{-(4 x) + y = 1 | (equation 1)

{0 x+y/2 = (-1)/2 | (equation 2)

Multiply equation 2 by 2:

{-(4 x) + y = 1 | (equation 1)

{0 x+y = -1 | (equation 2)

Subtract equation 2 from equation 1:

{-(4 x)+0 y = 2 | (equation 1)

{0 x+y = -1 | (equation 2)

Divide equation 1 by -4:

{x+0 y = (-1)/2 | (equation 1)

{0 x+y = -1 | (equation 2)

Collect results:

Answer:  {x = -1/2 , y = -1